2023
DOI: 10.24272/j.issn.2095-8137.2022.460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gradient high-field static magnetic fields on diabetic mice

Abstract: Although 9.4 T magnetic resonance imaging (MRI) has been tested in healthy volunteers, its safety in diabetic patients is unclear. Furthermore, the effects of high static magnetic fields (SMFs), especially gradient vs. uniform fields, have not been investigated in diabetics. Here, we investigated the consequences of exposure to 1.0–9.4 T high SMFs of different gradients (>10 T/m vs. 0–10 T/m) on type 1 diabetic (T1D) and type 2 diabetic (T2D) mice. We found that 14 h of prolonged treatment of gradient (as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In contrast, since SMFs are considered much safer and there are very limited safety studies, the guideline for SMFs was lastly published in 2009 and has not been updated since then. Besides this study, we also recently found that gradient high SMF (>10 T/m) could generate harmful effects on diabetic mice, especially for severe type 1 diabetic mice [ 44 ]. Since SMFs have the advantages of high penetration and no attenuation crosses the living organisms, they usually generate similar magnetic forces in small- or large-sized organisms because the molecules and cells are similar in size.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, since SMFs are considered much safer and there are very limited safety studies, the guideline for SMFs was lastly published in 2009 and has not been updated since then. Besides this study, we also recently found that gradient high SMF (>10 T/m) could generate harmful effects on diabetic mice, especially for severe type 1 diabetic mice [ 44 ]. Since SMFs have the advantages of high penetration and no attenuation crosses the living organisms, they usually generate similar magnetic forces in small- or large-sized organisms because the molecules and cells are similar in size.…”
Section: Discussionmentioning
confidence: 76%
“…We also found that high SMFs of 9.4 T exposure for 200 h did not have observable defects in tumor‐bearing mice 38 . However, 14 h of prolonged treatment of gradient high SMFs had negative effects on type 1 and 2 diabetes mice, including spleen, hepatic, and renal tissue impairment 39 . We have summarized the effect of long‐term SMF exposure in a book chapter recently, which can provide more information on this topic 40 .…”
Section: Discussionmentioning
confidence: 79%
“… 38 However, 14 h of prolonged treatment of gradient high SMFs had negative effects on type 1 and 2 diabetes mice, including spleen, hepatic, and renal tissue impairment. 39 We have summarized the effect of long‐term SMF exposure in a book chapter recently, which can provide more information on this topic. 40 The main purpose of this article is to investigate the effects of ultra‐high magnetic fields up to 33.0 T, hoping to provide information for the future development of high‐field MRI and other related devices, so our study was conducted at SMFs with four high or ultra‐high intensities, responding to the current demands for higher intensity magnetic fields in medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that magnetic fields (such as electromagnetic field and transcranial magnetic stimulation) are have potentials to reduce neuronal damage and cognitive impairment in AD (Arendash et al, 2010;Huang et al, 2017). Although prolonged treatment of high gradient magnetic field has been shown to have harmful effects on severe diabetic mice (Yu et al, 2023), the moderate intensity RMF have no reported side effects. By performing in vivo and in vitro experiments, we unravel that RMF can directly disrupt the Aβ assembly and reduce amyloid plaque deposition in the AD mice brain, which restored the motor ability and significantly alleviated the cognitive impairment in AD mice (Figure 7).…”
Section: Discussionmentioning
confidence: 99%